META SYNTHESIS OF STRATEGIC DEVELOPMENT MANAGEMENT BETWEEN INDONESIA AND AUSTRALIA BASED ON CONSTANT MARKET SHARE PERSPECTIVE - Gunawan Wibisono; Nanik Kustiningsih; Lanny Regina Susanti (Media Mahardhika, 2023)
The conditions of intense competition in the international market have encouraged Indonesia to be able to compete with other export products from other countries. One of the simple solutions is that the export products that are sold must be of very high quality and take advantage of the empty gaps in the international market. The main way is to fully optimize from viewing and analyzing market strategies. So the nature of our trade will look more offensive to the industrial economy. The use of FTAs is only for reducing tariffs and helping the flow of goods, but Indonesia must also be able to provide encouragement intensively so that these goods can win in one of the FTA areas. The solution presented is directing or piloting starting from one type of export goods. The author observes that the strategy or stages planned with method of meta synthesis. Indonesia are effective in the potential to increase and win Indonesian export products. First, studies by providing solutions on how Indonesian export products can compete and win in one of their destination countries. Second, deepening in the export market shows market power and sends market intelligence to make observations to the micro scale regarding export products and analysis of every policy and solution issued to that country. Third, the overall implementation and application of policy solutions to win Indonesian export products. One of the mistakes made at the implementation stage was said to be exports that were not quite right by Australia.